Capital cost evaluation of conventional and emerging redox flow batteries for grid storage applications. (1st January 2023) - Tang, L.; Leung, P.; Mohamed, M.R.; Xu, Q.; Dai, S.; Zhu, X.; Flox, C.; Shah, A.A.; Liao, Q.
Abstract: Redox flow battery (RFB) is a promising technology to store large amounts of energies in liquid electrolytes attributable to their unique architectures. In recent years, various new chemistries have been introduced in both aqueous and non-aqueous electrolytes as pathways to lower-cost systems, eventually meeting the long-term cost target of USD$ < 100 (kW h) −1 for board market penetration. Since there is a lack of capital cost data available for flow batteries under the same criteria and assumptions, a fact-based techno-economic analysis is evaluated based on real systems to facilitate the explorations of more competitive systems. In total, nine conventional and emerging flow battery systems are evaluated based on aqueous and non-aqueous electrolytes using existing architectures. This analysis is attempted to evaluate the feasibility of these emerging systems to meet the cost target and to predict their technological prospects for energy storage applications. The capital costs of these resulting flow batteries are compared and discussed, providing suggestions for further improvements to meet the ambitious cost target in long-term.